Insulin‐like growth factor 1 and dehydroepiandrosterone levels in alcoholic liver cirrhosis. Issue 10 (30th August 2022) - Dammermann, Werner; Seckinger, Benedikt; Füller, David; Lüth, Stefan; Hentschel, Florian
Abstract : Anabolic hormones in liver cirrhosis are suspected to be lower than in healthy individuals. In a group of 22 cirrhosis patients, we found lower levels of insulin‐like growth factor 1, but—surprisingly—higher levels of dehydroepiandrosterone.